Glaucoma secondary to intraocular tumors key aspects of etiopathogenesis - A.A. Yarovoy; T.V. Sokolovskaya; E.O. Krasnova; A.D. Matyaeva (Офтальмохирургия)
Purpose. To analyze the literature on the main aspects of etiology, pathogenesis of secondary glaucoma in tumor diseases of visual organs. Material and methods. PubMed, Scopus and eLIBRARY databases for the period up to 2022 were used for article selection, and the following keywords were used in the mesh: secondary glaucoma, tumor, neovascularization, pigment dispersion (and the same phrases in Russian). Results. The literature review presents various pathological mechanisms of developing secondary glaucoma. The reasons of decreased outflow of intraocular fluid of drainage and embedded (uveoscleral) pathways, lead to the increase of intraocular pressure in neoplastic glaucoma and depend on the type of eye tumor, its localization and size. This determines the necessity for a differentiated approach to the treatment of patients with secondary glaucoma and the development of pathogenetically oriented methods of treatment. Conclusion. Almost all of the intraocular tumors can potentially lead to increase of intraocular pressure. The pathomechanisms of neoplastic glaucoma are very diverse, but the leading ones are blocking of the anterior chamber angle drainage zone by tumor, neovascularization of the anterior chamber angle structures and anterior iris-lens diaphragm displacement. In all cases, the increase in intraocular pressure is associated with the violation of aqueous humor outflow through the main drainage paths of the eye. Currently, secondary glaucoma is not given enough attention, but this problem is extremely relevant in ophthalmology.